1996
DOI: 10.1002/j.1552-4604.1996.tb04223.x
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Efficacy of Controlled‐Release Oxycodone in Postoperative Pain

Abstract: The efficacy and safety of graded doses (10, 20, and 30 mg) of controlled-release (CR) oxycodone was compared with that of immediate-release (IR) oxycodone (15 mg), immediate-release oxycodone 10 mg in combination with acetaminophen 650 mg (APAP), and placebo in a single-dose, double-blind, randomized, parallel-group study. The participants, 182 inpatients experiencing moderate to severe pain after abdominal or gynecologic surgery, provided hourly ratings of pain intensity and relief for 12 hours after adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
1
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 15 publications
4
75
1
2
Order By: Relevance
“…In contrast with these results, Jokela et al [12] have recently shown that premedication with controlledrelease oxycodone does not improve management of postoperative pain after day-case gynecological laparoscopic surgery. Controlled-release oxycodone has shown high bioavailability, which contributes to modest interindividual variability after oral administration [13]. Moreover, the controlled-release formulation improves patient compliance when compared with immediate-release oxycodone [9], as it needs to be taken rarely, only twice or three times a day.…”
mentioning
confidence: 99%
“…In contrast with these results, Jokela et al [12] have recently shown that premedication with controlledrelease oxycodone does not improve management of postoperative pain after day-case gynecological laparoscopic surgery. Controlled-release oxycodone has shown high bioavailability, which contributes to modest interindividual variability after oral administration [13]. Moreover, the controlled-release formulation improves patient compliance when compared with immediate-release oxycodone [9], as it needs to be taken rarely, only twice or three times a day.…”
mentioning
confidence: 99%
“…Predictable pharmacokinetics, rapid onset of action, no ceiling dose, and minimal adverse effects contributed to its successful use in the treatment of postoperative pain [5][6][7][8] . A low incidence of nausea and vomiting compared to other opioids was found in some studies [9,10] , with controlled-release oxycodone causing fewer adverse events than immediate-release oxycodone [3,7,11] .…”
mentioning
confidence: 99%
“…We observed that the commonly reported opioid side effects 6,[31][32][33][34] were present with both regimens, namely, somnolence, dizziness, pruritus, nausea and vomiting. Respiratory depression, one of the most concerning side effects of opioid medications, was not observed in either group, nor were there any acetaminophen-related side effects, including hepatotoxicity.…”
Section: Discussionmentioning
confidence: 88%